2017
DOI: 10.1155/2017/3619721
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Complexity of Deliberate Self-Poisoning through Network Analysis

Abstract: The purpose of this research was to examine the complexity of circumstances that result in deliberate self-poisoning cases. For the purposes of this paper, the cases were patients that presented for care and were admitted to the specialty hospital in Northwest of Iran. The research examined the problems preceding deliberate self-poisoning and the interrelations among them by applying network analysis methods. The network was scored for degrees of centrality and betweenness centrality. Structural analysis of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Intentional self-poisoning occurs globally across all levels of income [5] , [6] . These self-harm episodes are not accidents; they are deliberate actions taken by patients to escape from complex and distressing life circumstances [7] . A population-based cohort study also indicated that intentional self-poisoning is a strong predictor of subsequent suicide (23%) and even premature death [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Intentional self-poisoning occurs globally across all levels of income [5] , [6] . These self-harm episodes are not accidents; they are deliberate actions taken by patients to escape from complex and distressing life circumstances [7] . A population-based cohort study also indicated that intentional self-poisoning is a strong predictor of subsequent suicide (23%) and even premature death [8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these barriers might be overcome by using network analysis but, to our knowledge, no independent study has employed this approach to studies of Li response. Network analysis describes a set of procedures based on the modelling of dynamic systems, and it has been employed recently in several high‐profile studies of inter‐relationships between symptoms . The technique provides a graphical representation of nodes (individual factors, objects, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The technique provides a graphical representation of nodes (individual factors, objects, etc.) and edges (associations, connections or links among those factors) and can be applied to many sets of items, including life events associated with suicide attempts and factors associated with treatment response (e.g. ).…”
Section: Introductionmentioning
confidence: 99%